Waste management in the international legal regime on climate change (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It addresses waste management from a life cycle and circular economy perspective, demonstrating its high potential for emission reduction and advocating for its centrality in the discussions of the Paris Agreement and COP-30.(Received: September 2025 | Accepted: October 2025)
Keywords: Waste Management; Circular Economy; Paris Agreement; Climate Change; GHG Emissions